Recent trends of minor export crops in matale district - Sabitha, S.; Subajini, U. (University of Jaffna, 2019)
The plantation of minor export crops has become a prominent agriculture activity in Matale. Such crops include pepper, cinnamon, cloves, arecanut, betel, cocoa, coffee, nutmeg, cardamom, ginger and turmeric. Where the cultivation of these crops has been an important activity in this region no geographical studies appear to have been made so far based on the recent trends of these minor export crops. In this regard, this study objects at knowing about the cultivation of minor export crops during the period from 2008 to 2017 and the changes that took place in these exports. This study also ventures to identify the various problems encountered in these exports and attempts to suggest solutions to remedy them. With this vision in mind the primary data for this study were obtained through group discussions, interviews and direct observations. In addition secondary data having been abstained from exports the agriculture department, the ministry for encouraging minor export crops exportation, the extent of cultivation change in prices, the recent stagnations in price faced by cultivators and the diseases affecting crops. The recent challenges faced by these crops have also been included into the conclusions. On this basis, solution and recommendation have been put forward such as increasing the standard of crop cultivation, conversion of products into finished export items government and private sector acting in co-ordination increasing the activities of the small exports department, offering pension and other incentives to those engaged in these activities in order to encourage and promote this minor export crop cultivation. In addition this study should immensely help future researches on minor export crop cultivation.
Keywords: Minor export crops; Production; Export; Stagnation; Income